2011
DOI: 10.1002/etc.464
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and bioaccumulation of phenanthrene inEnchytraeus albidus(Oligochaeta: Enchytraeidae)

Abstract: Polycyclic aromatic compounds, such as phenanthrene (PHE), tend to accumulate in the soil compartment, where they may be retained for many years because of their persistency and hydrophobicity. The toxicity and bioaccumulation of these chemicals in soil biota and potential biomagnification along the food chain is an issue of concern. The main goal of this study was to determine the toxicity and bioaccumulation of PHE in Enchytraeus albidus (Oligochaeta: Enchytraeidae) in a natural standard soil (LUFA 2.2) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
0
12
2
Order By: Relevance
“…Also, in the present study, the reproduction EC50 value of 13 580 mg/kg NaCl (corresponding to an electrical conductivity of 10.4 dS/m) was obtained, whereas for the earthworm E. fetida, reproduction EC50 values of 2020 mg/kg corresponding to an electrical conductivity value of 0.67 dS/m were reported [43]. For the collembolan F. candida, reproduction EC50 values between 0.52 and 1.03 dS/m were reported in natural loamy soil collected from Western Cape, South Africa [44] For phenanthrene, the reproduction EC50 value of 66 mg/kg derived here in OECD soil of 5% organic matter is many-fold lower than 257 mg/kg derived for F. candida in LUFA 2.2 soil [24] and 175 mg/kg in OECD soil of 10% organic matter [45] but 2-fold higher than the reproduction EC50 of 33 mg/kg reported for Enchytraeus albidus in LUFA 2.2 soil [46]. For the earthworm E. fetida, an LC50 of 40.67 mg/kg reported [47] was lower than 684 mg/kg obtained for H. aculeifer in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Also, in the present study, the reproduction EC50 value of 13 580 mg/kg NaCl (corresponding to an electrical conductivity of 10.4 dS/m) was obtained, whereas for the earthworm E. fetida, reproduction EC50 values of 2020 mg/kg corresponding to an electrical conductivity value of 0.67 dS/m were reported [43]. For the collembolan F. candida, reproduction EC50 values between 0.52 and 1.03 dS/m were reported in natural loamy soil collected from Western Cape, South Africa [44] For phenanthrene, the reproduction EC50 value of 66 mg/kg derived here in OECD soil of 5% organic matter is many-fold lower than 257 mg/kg derived for F. candida in LUFA 2.2 soil [24] and 175 mg/kg in OECD soil of 10% organic matter [45] but 2-fold higher than the reproduction EC50 of 33 mg/kg reported for Enchytraeus albidus in LUFA 2.2 soil [46]. For the earthworm E. fetida, an LC50 of 40.67 mg/kg reported [47] was lower than 684 mg/kg obtained for H. aculeifer in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Avoidance behavior is an ecologically relevant endpoint, which is well-useable in soil ecotoxicology tests with Annelids [40,65,66]. When the behavior or tolerance of potworms was examined, it was typical that the sublethal end-points (bioaccumulation, reproduction avoidance) were more sensitive compared to lethality [12,40,67].…”
Section: Avoidance Testsmentioning
confidence: 99%
“…This may be explained by uptake kinetics, but to our knowledge, such data are not available for uptake of phenanthrene in F. candida. However, Amorim et al [13] studied the kinetics of phenanthrene in the enchytraeid E. albidus and showed that phenanthrene was highly accumulated, with a bioaccumulation factor of 20.8 kg soil/kg fresh weight animal. The uptake kinetics were fast, with a steady state being reached within 10 d. Shi et al [24] showed that the internal phenanthrene concentration also reached a maximum within 5 d to 14 d in the earthworm Eisenia fetida, depending on the initial phenanthrene exposure concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Castro-Ferreira et al [6] showed that a 10% decrease in reproduction of E. crypticus may already be observed at a phenanthrene concentration of 37 mg/kg soil, indicating its potent and environmentally relevant toxicity. Further studies showed, for example, a high bioaccumulation potential of phenanthrene in Enchytraeus albidus as compared to earthworms [13]. A microarray was developed based on transcriptomic information [5], to study the molecular mechanistic consequences of soil pollution.…”
Section: Introductionmentioning
confidence: 99%